Artemisia spp. essential oils against the disease-carrying blowfly Calliphora vomitoria. Issue 1 (December 2017) - Bedini, Stefano; Flamini, Guido; Cosci, Francesca; Ascrizzi, Roberta; Echeverria, Maria; Guidi, Lucia; Landi, Marco; Lucchi, Andrea; Conti, Barbara
Abstract Background Synanthropic flies play a considerable role in the transmission of pathogenic and non-pathogenic microorganisms. In this work, the essential oil (EO) of two aromatic plants, Artemisia annua andArtemisia dracunculus, were evaluated for their abilities to control the blowflyCalliphora vomitoria. Artemisia annua andA. dracunculus EOs were extracted, analysed and tested in laboratory bioassays. Besides, the physiology of EOs toxicity and the EOs antibacterial and antifungal properties were evaluated. Results BothArtemisia EOs deterredC. vomitoria oviposition on fresh beef meat. At 0.05 μl cm-2 A. dracunculus EO completely inhibitedC. vomitoria oviposition. Toxicity tests, by contact, showed LD50 of 0.49 and 0.79 μl EO per fly forA. dracunculus andA. annua, respectively. By fumigation, LC50 values were 49.55 and 88.09 μl l-1 air forA. dracunculus andA. annua, respectively. EOs AChE inhibition inC. vomitoria (IC50  = 202.6 and 472.4 mg l-1, respectively, forA. dracunculus andA. annua ) indicated that insect neural sites are targeted by the EOs toxicity. Finally, the antibacterial and antifungal activities of the twoArtemisia EOs may assist in the reduction of transmission of microbial infections/contaminations. Conclusions Results suggest thatArtemisia EOs could be of use in the control ofC. vomitoria, a common vector of pathogenic microorganisms and agent of human and animal cutaneous myiasis. The prevention of pathogenic and parasitic infections is a priority for human and animal health. TheArtemisia EOs could represent an eco-friendly, low-cost alternative to synthetic repellents and insecticides to fight synanthropic disease-carrying blowflies.